The Effectiveness of Nonviolent Communication Program Training on Mother-Child Interaction in Mothers of Children With Intellectual Disability - Zahra Rezaei; Ahmad Behpajooh; Bagher Ghobari-Bonab (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Besides their communication and socialization problems, many children with Intellectual Disability (ID) have difficulties with their parents, siblings, and teachers. The enduring nature of social reactions easily leads to social isolation. Thus, many children and adults with ID have few friends, even though they may desperately want to be liked. This can set up a vicious circle in which they attempt to win friends by latching onto the least chance for interaction with others. Regarding the characteristics of nonviolent communication program training, it seems that this program could reduce communication problems and improve mother-child interaction of children with ID. The nonviolent communication training program is one method for improvement of communication skills in parents of the children with ID because these parents are often facing problem in communication with their children. Nowadays, much effort is made for improving mother-child interaction, especially in mothers of children with ID. Therefore, the purpose of the present study was to investigate the effect of nonviolent communication program training on mother-child interaction in mothers of children with ID. Materials & Methods The present research was a quasi-experimental study with pretest-posttest and a control group. The study population included all of the mothers of children with ID who attend to Alborz Educational and Rehabilitation Institute which is located in Alborz Province, Iran under the supervision of welfare organization. The study sample included 30 mothers selected by convenience sampling method and assigned to two groups. The experimental group participated in a communication skills training program based on life language for 8 sessions (90 minutes for per session; twice a week), while the control group received no such training. The study instrument was the Pianta mother-child interaction scale (1992). The Pianta mother-child interaction scale was completed by mothers for all subjects in pretest and posttest. The study data were collected through the questionnaire before and after the training sessions. Multivariate analysis of covariance was performed in SPSS (Version 22) for analyzing the obtained data. Results First, the normality of study variables and contingency of variance and covariance assumptions were tested. The Kolmogorov-Smirnov test showed that all variables were normally distributed (P>0.05). Also, the Box test confirmed the contingency of variance-covariance assumption. So, assumptions of the MANCOVA test were confirmed and MANCOVA test can be used for analysis of data. The results of MANCOVA revealed that posttest scores of experimental and control groups had a significant difference with regard to mother-child interaction (P<0.001). Also, the results of MANCOVA revealed that posttest scores of experimental and control groups had a significant difference with regard to conflict, closeness, and dependency subscales (P<0.001). It can be stated that according to Eta2, 67% of the variance in mother-child interaction can be explained by the subjects' participation in the nonviolent communication training program. Also, according to Eta2, respectively 63%, 65%, and 66% of the variance in components of conflict, closeness, and dependency can be explained by the subjects' participation in the nonviolent communication training program. Therefore, communication skills training based on life language has a positive effect on mother-child interaction of the mothers of children with ID. Conclusion Parents of children with ID has more problems in communication with their children than parents of any other kind of exceptional children. It doesn't take long that these children be ostracized from social activities. Unfortunately, the negative social status experienced by children with ID is difficult to overcome and usually long-lasting. Nonviolent communication program training improves mother-child interaction in mothers of children with ID. Therefore, providing nonviolent communication program training has particular importance for these mothers.